What makes a good English teacher in the context of teaching English as a global language? - Phulakor, Jatupon (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 10 No 1 (2018): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2021)
This article aims at providing the important qualities of a good English teacher including personal characteristics, positive beliefs about English language teaching and self-efficacy. These qualities will be useful for preparing a good English teacher to teach in the context of teaching English as a Global Language.